The Political Economy of Television Sports Rights - Evens, T. author. aut Link
XIII, 267 p.
Keywords: Sport on television is big business, but it is about more than just commerce. Using a range of national case studies from Europe and beyond, this book analyses the political, economic, social and regulatory issues raised in relation to the buying and selling of television sports rights.